Environmental Management and Protection Based on The Green Constitution Concept - Ardina Nur Amalia; Rahayu Rahayu (Magister of Law, Faculty of Law, University of Mataram, 2021)
This study aimed to analyze the green constitution concept as the basis for environmental protection and management in Indonesia. Various problems that occur such as natural disasters, ecosystem damage, and global warming raise concerns and ecological awareness. The problem discussed in this research was what is the importance of implementing the green constitution concept and how it is applied in Indonesia. This research was normative legal research using secondary data. Based on the results of the study, it was concluded that it requires sustainable development-based development for the sustainability of human life, as well as other living creatures on earth. The program is in line with the concept of the Green Constitution. This concept has been embraced by several countries, including Indonesia,the Green Constitution concept is adopted in Indonesia with recognition to the concept in the Constitution of the Republic of Indonesia, which is then relegated to laws and regulations under it.